Apical Bud Pinching and Foliar Spray of Zinc and Boron Triggers Growth and Yield of Okra (Abelmoschus esculentus L.) - Basanta Bhattarai; Madhav Neupane; Rijwan Sai; Bikram K.C.; Yuvraj Basnet; Arjun Giri (Turkish Journal of Agriculture: Food Science and Technology)
Okra (Abelmoschus esculentus) cultivation in regions like Ramechhap, Bagmati Province, Nepal faces challenges in improving yield and economic returns due to suboptimal agronomic practices. To address this issue, a field experiment was conducted to assess the effects of pinching and micronutrient sprays (zinc and boron) on growth, yield, and economic returns of okra. The study aimed to evaluate the impact of pinching and zinc-boron foliar application on key growth parameters, including the number of leaves, fruit length, number of fruits per plant, and total yield. Pinching significantly increased the number of leaves and fruits per plant, as well as the total yield. The application of 0.25% Zn + 0.25% B resulted in the highest fruit length, fruit weight, and total yield. The combined treatment of pinching and Zn-B spray (P1M3) recorded the highest fruit length (11.13 cm), number of fruits per plant (21.91), and yield (17.68 t ha-1). Economic analysis revealed that this combination resulted in the highest net return (NRs. 774,869.35 ha-1) and the highest benefit-cost ratio (B:C = 1.95), indicating that it could significantly improve farm income for smallholder farmers in the region. These results demonstrate the potential of integrated agronomic practices, including pinching and micronutrient application, to enhance both productivity and profitability in okra cultivation.